2018
DOI: 10.1111/nph.15109
|View full text |Cite
|
Sign up to set email alerts
|

The RecQ‐like helicase HRQ1 is involved in DNA crosslink repair in Arabidopsis in a common pathway with the Fanconi anemia‐associated nuclease FAN1 and the postreplicative repair ATPase RAD5A

Abstract: RecQ helicases are important caretakers of genome stability and occur in varying copy numbers in different eukaryotes. Subsets of RecQ paralogs are involved in DNA crosslink (CL) repair. The orthologs of AtRECQ2, AtRECQ3 and AtHRQ1, HsWRN, DmRECQ5 and ScHRQ1 participate in CL repair in their respective organisms, and we aimed to define the function of these helicases for plants. We obtained Arabidopsis mutants of the three RecQ helicases and determined their sensitivity against CL agents in single- and double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 70 publications
(142 reference statements)
5
21
0
Order By: Relevance
“…Knock-down mutants display leaf chlorosis and activation of multiple stress responses [49]. In the network, AtGLU1 interacts with the GWES candidate genes Glyma.05 g127900 (At1G72550), a tRNA synthase, and Glyma.06 g206600 (At5G08110/AtHRQ1), which is required for genome stability and repair [79]. These results provide further support for our epistatic analyses.…”
Section: Iron Deficiency and Epistasissupporting
confidence: 70%
“…Knock-down mutants display leaf chlorosis and activation of multiple stress responses [49]. In the network, AtGLU1 interacts with the GWES candidate genes Glyma.05 g127900 (At1G72550), a tRNA synthase, and Glyma.06 g206600 (At5G08110/AtHRQ1), which is required for genome stability and repair [79]. These results provide further support for our epistatic analyses.…”
Section: Iron Deficiency and Epistasissupporting
confidence: 70%
“…Furthermore, sensitivity studies revealed that MUS81 is strongly involved in the repair of DNA crosslinks and alkylations induced by the genotoxic agents mitomycin C, cis-platin, methyl methanesulfonate, and ionizing radiation (Hartung et al, 2006;Berchowitz et al, 2007;Mannuss et al, 2010). Epistasis analysis indicated that the endonuclease MUS81 acts independently of the ATPase RAD5A and the DNA helicases HRQ1 and RTEL1, as well as the Translesion Polymerase zeta in the repair of cis-platin-induced damage (Mannuss et al, 2010;Recker et al, 2014;Kobbe et al, 2015;Röhrig et al, 2018). Detection of synthetically lethal phenotypes of mus81-1 lines, additionally lacking one of the helicases RECQ4A or Fanconi anaemia complementation group M protein, explicitly demonstrated that MUS81 is crucially needed for the repair of replicationassociated DNA damage (Hartung et al, 2006;Mannuss et al, 2010;Dangel et al, 2014;Dorn et al, 2018).…”
Section: Wss1a Mus81 and Tdp1 Define Different Pathways Of Dpc Repamentioning
confidence: 99%
“…Furthermore, a role in ICL repair has been demonstrated for the RTR complex partner TOP3α, hinting to a joint involvement of the complex [159]. Interestingly, a RecQ-like helicase HRQ1, which is proposed to be the yeast and plant homologue to human RECQ4, was recently demonstrated to act in ICL repair in Arabidopsis wherein a role parallel to RECQ4A and similar to that of RAD5A was revealed [160]. Furthermore, HRQ1 and RAD1 were proposed to cooperate in ICL repair, indicating the possibility of another helicase nuclease association for the initial repair steps.…”
Section: Repair Of Intrastrand Cls and Iclsmentioning
confidence: 99%
“…In the same study, a hidden role for the FA helicase FANCM was also defined as acting in parallel to RTEL1. Furthermore, a role in intrastrand CL repair was confirmed for the FA-associated nuclease FAN1 [160]. PRR is an important mechanism for the repair of intrastrand CLs, reflecting the importance of both RAD5A and REV3 in Arabidopsis [157,165].…”
Section: Repair Of Intrastrand Cls and Iclsmentioning
confidence: 99%